2023
DOI: 10.1038/s41598-023-30668-y
|View full text |Cite
|
Sign up to set email alerts
|

Concussed patients with visually induced dizziness exhibit increased ocular torsion and vertical vergence during optokinetic gaze-stabilization

Abstract: Visually Induced Dizziness (VID) is a common post-concussion sequalae that remains poorly understood and difficult to quantify. The present study aims to identify biomarkers for VID in the form of gaze-stabilizing eye movements. Nine patients with post-commotio VID and nine age-matched healthy controls were recruited by physiotherapists at a local neurorehabilitation centre. Torsional and vergence eye movements were recorded while participants viewed a series of optokinetic rotations where the central- and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…VV is also increased during monocular viewing compared to binocular conditions, meaning that it likely serves a fusional purpose as it is supressed during binocular viewing (Wibble and Pansell 2020 ). We have also described how visually induced VV is affected in concussed patients suffering from vestibular symptoms of vertigo or dizziness to visual motion (Wibble et al 2023 ; Frattini et al 2024 ). The relationship between torsion and vergence during vestibular movements appears to remain relatively constant by comparison (Wibble and Pansell 2019 ; Wibble et al 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VV is also increased during monocular viewing compared to binocular conditions, meaning that it likely serves a fusional purpose as it is supressed during binocular viewing (Wibble and Pansell 2020 ). We have also described how visually induced VV is affected in concussed patients suffering from vestibular symptoms of vertigo or dizziness to visual motion (Wibble et al 2023 ; Frattini et al 2024 ). The relationship between torsion and vergence during vestibular movements appears to remain relatively constant by comparison (Wibble and Pansell 2019 ; Wibble et al 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…This response can also be altered depending on the visual content; increased visual clutter will increase the relative gain of torsion over vergence (Wibble and Pansell 2019 ), while heightened accelerations will lead to an inverse shift (Wibble et al 2020a ). These eye movement responses are also affected by cognitive states such as alertness or attention (Frattini and Wibble 2021 ; Magnusson et al 1985 ), and they have been shown to act as promising biomarkers for visual processing disorders following concussion (Wibble et al 2023 ; Bertolini et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 16 Concussion has been shown to alter the visual information pathways across the brain, ranging from the basal ganglia to several cortical areas. 17 , 18 It is also known that concussion can lead to maladaptive gaze control, influencing both voluntary gaze shifts 19 and optokinetic gaze stabilization, 9 , 20 indicating a mechanism of injury that can influence both fundamental subcortical motion integration as well as higher level sensory processing. It has been proposed that this increased responsiveness to visual cues leads to sensory reweighing, where visual motion gains in relevance compared to the mismatched vestibular input.…”
mentioning
confidence: 99%